2017
DOI: 10.1088/1361-6560/aa96d0
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical wave imaging and electromechanical wave velocity estimation in a large animal model of myocardial infarction

Abstract: Background Echocardiography is often used in the clinic for detection and characterization of myocardial infarction. Electromechanical wave imaging (EWI) is a non-invasive ultrasound-based imaging technique based on time-domain incremental motion and strain estimation that can evaluate changes in contractility in the heart. In this study, electromechanical activation is assessed in infarcted heart to determine whether EWI is capable of detecting and monitoring infarct formation. Additionally, methods for estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…where T T x x = ¶ ¶ / and T T y. y = ¶ ¶ / 33,46) Because the local and two-dimensional propagation speed of myocardial contraction was estimated although only the average speeds were estimated in our previous study, 23,31,32) the estimation of spatial distribution of the propagation speed vectors became possible.…”
Section: Propagation Speed Estimation Of Myocardial Contraction Responsementioning
confidence: 99%
See 1 more Smart Citation
“…where T T x x = ¶ ¶ / and T T y. y = ¶ ¶ / 33,46) Because the local and two-dimensional propagation speed of myocardial contraction was estimated although only the average speeds were estimated in our previous study, 23,31,32) the estimation of spatial distribution of the propagation speed vectors became possible.…”
Section: Propagation Speed Estimation Of Myocardial Contraction Responsementioning
confidence: 99%
“…Displacement waveforms obtained by integrating the velocity waveforms are also shown. Although several studies have reported the detection of myocardial contraction using displacement waveforms, 7,8,19,27,28,30,[44][45][46] it is possible to measure not only the visible contraction but also minute vibrations caused by contraction using velocity waveforms. The contraction response at the time of the electrocardiographic QR interval representing the onset of ventricular contraction can be identified as the bimodal movements of myocardium toward the LV, i.e., the bimodal positive waveform in velocity waveforms, although the displacement waveforms were almost smooth.…”
Section: Measurement Of Velocity With Minute Vibrations In the Myocar...mentioning
confidence: 99%